2013
DOI: 10.1088/1475-7516/2013/05/034
|View full text |Cite
|
Sign up to set email alerts
|

Interacting warm dark matter

Abstract: We explore a cosmological model composed by a dark matter fluid interacting with a dark energy fluid. The interaction term has the non-linear λρ α m ρ β e form, where ρ m and ρ e are the energy densities of the dark matter and dark energy, respectively. The parameters α and β are in principle not constrained to take any particular values, and were estimated from observations. We perform an analytical study of the evolution equations, finding the fixed points and their stability properties in order to character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…Thus, the effective "warm dark matter" from type I models of the varying cosmological constant ∝ α −6 is fully consistent with the observational constraints on WDM (e.g. [79][80][81][82][83][84][85][86][87][88]109]). …”
Section: Varying Cosmological Constant and Warm Dark Mattersupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the effective "warm dark matter" from type I models of the varying cosmological constant ∝ α −6 is fully consistent with the observational constraints on WDM (e.g. [79][80][81][82][83][84][85][86][87][88]109]). …”
Section: Varying Cosmological Constant and Warm Dark Mattersupporting
confidence: 69%
“…In the literature, many attempts have been made to determine the EoS of dark matter (see e.g. [79][80][81][82][83][84][85][86][87][88]), and it is found that the EoS of WDM are of O(10 −6 ), O(10 −5 ) or O(10 −3 ) (depending on the working assumptions and the observational data in use).…”
Section: Varying Cosmological Constant and Warm Dark Mattermentioning
confidence: 99%
“…Following the method, the authors in [17] found that the value of the EoS parameter of DM is consistent with pressureless DM within the errors. The authors of [18,19] investigated the "warmness" of the DM fluid constraining cosmological models with constant EoS parameters of DM and DE by considering noninteracting and interacting scenarios of DM and DE. The authors in [20] considered various cosmological models consisting of only DM and DE components by assuming constant and variable EoS parameters of the two components.…”
Section: Introductionmentioning
confidence: 99%
“…Faber & Visser (2006) and Serra & Romero (2011) have constrained the EoS of DM by combining kinematic and gravitational lensing data. The warmness of DM has also been investigated in interacting and non-interacting scenarios of DM and DE by assuming constant EoS of both DM and DE in Avelino et al (2012) and Cruz et al (2013). Many models of DM and DE have been constrained by assuming constant as well as variable EoS parameter of DM and DE in Wei et al (2013), where the authors have found that warmness of DM is not favored over coldness in the light of data from CMB, SNe Ia and baryonic acoustic oscillations (BAO).…”
Section: Introductionmentioning
confidence: 99%